Παραμετρική μελέτη θέρμανσης χώρων με ηλιακή ενέργεια με χρήση του προγράμματος F-Chart - Κούτρα, Νίτσα (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Nowadays, with the rapid development of technology, we managed to make our lives theoretically easier, creating though more problems.This is mainly due to the lack of responsibility with which we face new achievements.The modern person overuses the limitless strengths which were given to him from this development, without thinking that he is responsible for the problems which strike the planet.In our days, there is a lot of concern about the environmental problems.One of the ways of dealing with the problems is the use of Renewable Sources of Energy (RES).The RES can provide alternative ways to produce energy with mild effects towards the environment.There are many types of RES like solar, aeolian, biomass, hydroelectric and geothermal energy which are widely used today.In this dissertation, one of the most popular renewable sources of energy, solar energy, is being analyzed.Solar energy is a clean, mild, and inexhaustible source of energy, which is abundent in Cyprus.It can be used for either the production of thermal energy or for the generation of electricity.The objective of this dissertation is the analysis of the solar behavior of a solar heating system, which has been designed to cover the needs of a typical residential house in Cyprus.The system is applied in different geographical areas of Cyprus, representing the four climate zones of Cyprus, defined by the Cyprus Meteorological Service.These zones cover the coastal, lowland, semi-mountainous and mountainous areas.The analysis of the system is done parametrically changing the surface of the collectors, the volume of the storage tank and other important parameters, including the economic parameters, using the F-CHART program.The simulation results obtained from F-CHART demonstrate that the residential house located in the mountainous area has the highest demand for space heating and domestic hot water production, resulting to high cost in the heating fuel.A solution to the increased costs in fuel is the investment in installing the solar heating system with the use of flat plate solar collectors.From this investment, a long term profit is achieved, since the costs of the auxiliary source of energy (fuel oil) which will be needed throughout the 20 years of operation of the system, is three times less than the cost without it.This is not only noticeable in the mountainous area but also in the rest of the climate zones to a lesser degree.Therefore, the investment in such a system is obviously profitable according to the results obtained from the simulations conducted by the F- Chart program.
Keywords: Renewable Sources of Energy; Solar energy; F- Chart program; Ανανεώσιμες πηγές ενέργειας; Ηλιακή ενέργεια; πρόγραμμα F-Chart